Relationship of training load with high-intensity running in professional soccer players - Lee, M.; Mukherjee, S. (International Journal of Sports Medicine, 2019)
This study determined the training load (TL) and its relationship with high-intensity running performance across the season in professional soccer players. The TL, YoYo Intermittent Recovery Test Level 2 (YYIR 2) and repeated sprint ability (RSA) were monitored in 29 players (age 26.2±3.8 years, height 173.6±5.6?cm, body mass 68.5±8.6?kg). In the mid in-season (MS), Lucia TRIMP (TRIMPL) was inversely correlated with YYIR 2 (r=-0.6, p<0.05), with total distance (TD), work-rate (WR), low-intensity distance (LID) and player load (PL) showing correlation with YYIR 2 (r=0.81, 0.77, 0.88, 0.67; p<0.05) in the late in-season (LS). In pre-season (PS), TD, WR and moderate-intensity distance (MID) were correlated with YYIR 2 (r=0.65, 0.80, 0.83, p<0.05), whereas in early in-season (ES), TD, WR, LID were correlated with YYIR 2 performance (r=0.58, 0.67, 0.55, p<0.05). There was no significant relationship (p>0.05) between TL and RSA. The findings showed the volume, intensity and types of TL accrued influences the relationship with physical performance that suggest the significance of phase-specific monitoring of TL for maximizing performance in soccer players.